“If only God would give me some clear sign!” - God, Religion, and Morality in Woody Allen’s Short Fiction - Precup, Amelia (Journal for the study of religions and ideologies, 2015)
Woody Allen’s uneasy relationship with organized religions, as represented in his entire work, has often drawn accusations of atheism and ethnic self-hatred, just as his personal behavior, as represented in the media, has stirred a series of allegations of immorality. However, Woody Allen’s exploration of religion, faith, and morality is far more complex and epitomizes the experience of modern man, living in a disenchanted universe. While most scholars focused on discussing the provocative debates over faith and religion in Woody Allen’s films, the main purpose of this paper is to investigate what underlies Woody Allen’s obsessive preoccupation with the existence of divinity, as expressed in that part of his work which received little critical attention, namely his short fiction. The purpose of such an analysis is not to clear Woody Allen’s vexed reputation, but to understand the relevance of his individual ideology for the religious and moral conundrums of modern man. The corpus selected for this analysis consists of a series of relevant short stories and essays published in the 1991 edition of The Complete Prose of Woody Allen, a volume which gathers the texts published in three other short story collections.